Improving Informed Consent with Minority Participants: Results from Researcher and Community Surveys - Quinn, Sandra Crouse (2012)
Strengthening the informed consent process is one avenue for improving recruitment of minorities into research. This study examines that process from two different perspectives, that of researchers and that of African American and Latino community members. Through the use of two separate surveys, we compared strategies used by researchers with the preferences and attitudes of community members during the informed consent process. Our data suggest that researchers can improve the informed consent process by incorporating methods preferred by the community members along with methods shown in the literature for increasing comprehension. With this approach, the informed consent process may increase both participants’ comprehension of the material and overall satisfaction, fostering greater trust in research and openness to future research opportunities.